Closure - Management, Journal of Infrastructure & Facility Asset (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Journal of Infrastructure & Facility Asset ManagementVolume 7, Special Issue 1, January 2025 (e) ISSN 2656-8896 (P) ISSN 2656-890X Volume 7, Special Issue 1, January 2025Parametric Study of Embankment Stability And Geotextile Reinforcement On Soft Soil Mirza Syah Alam, Herman Wahyudi, Yudhi Lastiasih, Yusrizal Kurniawan Analysis Of Slope Stability Based On The Effect Of RainFall On The Lombok International Airport (BIL) – Mandalika Road STA 10+375 to STA 10+550 Made Sudiadnya, Mohamad Khoiri, Dwa Desa Warnana, Herlambang Zulfikar Analysis of The Effect of Seismic Load on The Design Safety Factor of Foam Mortar with Bored Pile Landslide Location of Batas Pidie/Aceh Besar – Bts. Kota Sigli STA 0+560 Ichvan Danny Kurniawan, Trihanyndio Rendy Satrya, Ria Asih Aryani Soemitro, Fikri Afzal A Study of Pile Displacement in Soft Soil: The Case of Semarang - Demak Toll Road Construction Package 1B Novera Sagita, Herman Wahyudi, Yudhi Lastiasih &Yusrizal Kurniawan Design Of Toll Road Embankment With Secondary Compression Mitigation After PVD Installation And Solutions For The Probolinggo – Banyuwangi Toll Road Construction Project PackKAGE 2 STA 16+300 – STA 16+700 Septya Kukuh Aryandi, Indrasurya B. Mochtar, Noor Endah, Abdjad Agung ArtantoVolume 6, Special Issue 3, January 2024 Effect of Stabilization Soil With Fly Ash and Bottom Ash on Characteristics of Residual Soil (Padang-Sicincin Toll Road) Novema Dwi Saputra, Trihanyndio Rendy Satrya, Ria Asih Aryani Soemitro & Sri Hastuti HardiningsihEffect of Embankment Construction Pace on Slope Stability Wih Varied Heights on Organic Soft Soil in the Sicincin-Padang Toll Road Sta 10+250-10+400 Alfian Wildan Mulifandi, Trihanyndio Rendy Satrya, Ria Asih Aryani Soemitro & Sri Hastuti HardiningsihAnalysis Of Behavior And Chemical Stabilization Of Highly Plastic Local Excavated Soil for Embankments In The IKN Highway Project Segment 3A From Karangjoang To KKT Kariangau Mohammad Iqbal Yanuar, Herman Wahyudi, Yudhi Lastiasih & Dedi PrayitnoAnalysis of Embankment Slope Failure And Effectiveness Of Reinforcement With Full Displacement Column on Soft Soil (Case Study : Construction Of Padang Sicincin Toll Road Section STA 7+400 – 7+550) Firman Arifanto, Trihanyndio Rendy Satrya, Ria Asih Aryani Soemitro & Sri Hastuti Hardiningsih Effectiveness And Stability Analysis Of Embankment Using Lightweight Embankment On Pasuruan - Probolinggo Toll Road Project Section 4, Indonesia Ruri Febri Ritwandanu, Herman Wahyudi, Yudhi Lastiasih & Hamim Mufijar Comparation of Limit Equilibrium Method (LEM) 2D on Safety Factor and Embankment Reinforcement Aisiyah Pramaisela Hapsari & Yudhi Lastiasih